2015
DOI: 10.1016/j.rbmo.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates with intrauterine insemination: comparing 1999 and 2010 World Health Organization semen analysis norms

Abstract: Over the past 30 years, The World Health Organization has serially measured norms for human sperm. In this study, 1999 and 2010 semen analysis norms as predictors of pregnancy were compared during intrauterine insemination (IUI). A retrospective cohort study was conducted using data collected from the Stanford Fertility Center, between 2005 and 2007, with 981 couples undergoing 2231 IUI cycles. Collected semen was categorized according to total motile sperm counts (TMSC): 'normal (N.) 1999 TMSC', 'abnormal (Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…Although a semen analysis is the best predictive test we have to date, it clearly falls short of a true diagnosis (5,6). Indeed, several studies have shown that men with sperm numbers (7)(8)(9), morphology (8,10), and motility (11)(12)(13)(14)(15)(16)(17) below the thresholds outlined by the WHO can be fertile. Furthermore, there are many instances of men with normal sperm parameters that are infertile (13, 18 -20).…”
mentioning
confidence: 99%
“…Although a semen analysis is the best predictive test we have to date, it clearly falls short of a true diagnosis (5,6). Indeed, several studies have shown that men with sperm numbers (7)(8)(9), morphology (8,10), and motility (11)(12)(13)(14)(15)(16)(17) below the thresholds outlined by the WHO can be fertile. Furthermore, there are many instances of men with normal sperm parameters that are infertile (13, 18 -20).…”
mentioning
confidence: 99%
“…The results provide information on the functional status of the seminiferous tubules, epididymis and accessory sex glands [Esteves, 2014], which in turn influences the subsequent workup, treatment and outcomes [Baker et al 2015]. However, semen characteristics that discriminate between infertile and fertile men are not well defined and the clinical use of conventional semen parameters is far from perfect.…”
Section: Semen Analysismentioning
confidence: 99%
“…This is due, in part, to the fact that conventional semen analysis does not assess the diverse array of biological properties that spermatozoa express as eminent specialized cells, or account for putative sperm dysfunctions that can be assessed by sperm DNA damage or seminal oxidative stress tests [Duran et al 2002;Esteves, 2014;Papillon-Smith et al 2015].…”
Section: Semen Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies try to elucidate which standard semen parameters impact more on pregnancy rates for couples undergoing IUI, and it seems that sperm motility is the most predictive [6][7][8]. It must be remembered that Total Motile Sperm Count [TMSC] inseminated has been cited as the most predictive index of conception after IUI cycles [9][10][11]. A minimalTMSC of 1 million for insemination was initially reported to be a requirement for pregnancy after insemination [12], but the systematic review of the literature by Ombelet et al in 2014 indeed confirms that the native sperm TMSC which shows the best correlation with IUI success is in the range of 5-10 million [6,[13][14][15][16].…”
Section: Influence Of Semen Qualitymentioning
confidence: 99%